Endotoxin removal therapy with Polymyxin B immobilized fiber column as a COVID-19-bedside strategy protocol for endotoxic shock - De Rosa, Silvia; Zanella, Monica; Samoni, Sara; Ronco, Claudio (Frontiers in Nephrology, 2022)
Endotoxin-induced sepsis is a leading cause of ICU mortality. From 1994 to the present, 48 PMX-HP has been available as an adjuvant therapy for endotoxin removal and 49 immunomodulation. The efficacy and usefulness of this therapy have been demonstrated 50 for more than a quarter of a century and are partially supported by clinical studies. 51 However, it appears that selected subgroups of patients with endotoxic shock and with 52 appropriate timing could benefit. Endotoxemia may be involved in the pathophysiology of 53 COVID-19, based on enterocyte dysfunction and malabsorptive syndrome. Due to the 54 characteristics of the microbiota, Gram-negative bacteria or or their fragments (i.e., 55 endotoxin) may translocate into the systemic circulation leading to inflammatory 56 activation, immune dysfunction, and sepsis. In addition, patients with severe forms of 57 COVID-19 are at risk of superimposed infections. Endotoxemia can arise due to the 58 translocation of Gram-negative bacteria or their fragments from the gut barrier. According 59 to the most updated evidence available from large randomized trials, septic shock 60 patients with MODS > 9 and EA levels ranging from 0.6 to 0.9 are those who may benefit 61 the most from PMX‐HP treatment in terms of improvement of survival. As shown in a 62 previous publication, we believe that similarly to the source control, microbiological 63 cultures, and antibiotics administration, EA evaluation at regular intervals, and the 64 targeted use of PMX‐HP could be lifesaving and adequate within the golden hour for the 65 diagnosis and treatment of endotoxic shock. In our center, we applied a 66 diagnostic-clinical flowchart also for endotoxic shock related to COVID-19